PATIWANGI SANCTION IN BALINESE HINDU COMMUNITY’S LEGAL CULTURE - Ida Ayu Sadnyini (Fakultas Hukum Universitas Gadjah Mada, 2017)
AbstractInter-dynastic marriage today has been commonly held by Hindu community that has a vertically closed social stratification called dynasty. Couples who wants to perform inter-dynastic marriages before 1951 are required to conduct patiwangi ceremony in addition to the discharge penalty into areas outside Bali (Selong). Sanctions of patiwangi ceremony have been removed by some rules, but the community still conducts it. From this background, problems arise as follows: What is the meaning of patiwangi ceremony? Why are people still perform the patiwangi ceremony sanction?. The method used is the type of empirical legal research, using qualitative descriptive analysis. The meaning of patiwangi sanctions is to lower dignity and honor of a caste woman. People still perform the patiwangi because patiwangi is a legal culture that has penetrated into the soul of Hindu community in Bali.IntisariMakna sanksi upacara patiwangi adalah menurunkan derajat, kehormatan, keharuman wangsa dari perempuan yang memiliki wangsa brahmana, ksatria, dan weisya. Upacara patiwangi mengandung pelecehan baik dari segi sebutan istilah maupun pelaksaan upacara patiwangi. Oleh karena itu sudahsepantasnya upacara patiwangi dihapus, karena tidak sesuai dengan nilai-nilai kesetaraan, nilai-nilai kemanusiaan, nilai-nilai keadilan, dan nilai-nilai kearifan lokal. Berdasarkan hasil penelitian upacara patiwangi masih tetap dilakukan oleh masyarakat Hindu karena merasa yakin sanksi upacara patiwangi akan membawa keseimbangan dan kebaikan bagi pelaku perkawinan antar-wangsa. Upacara patiwangi sudah menjadi budaya hukum hukum bagi sebagian masyarakat Hindu di Bali.